An Epigenetic Perspective on the Midwife Toad Experiments of Paul Kammerer (1880–1926). Issue 1 (26th October 2016) - Vargas, Alexander O.; Krabichler, Quirin; Guerrero‐Bosagna, Carlos
ABSTRACT: Paul Kammerer was the most outstanding neo‐Lamarckian experimentalist of the early 20th century. He reported spectacular results in the midwife toad, including crosses of environmentally modified toads with normal toads, where acquired traits were inherited in Mendelian fashion. Accusations of fraud generated a great scandal, ending with Kammerer's suicide. Controversy reignited in the 1970s, when journalist Arthur Koestler argued against these accusations. Since then, others have argued that Kammerer's results, even if real, were not groundbreaking and could be explained by somatic plasticity, inadvertent selection, or conventional genetics. More recently, epigenetics has uncovered mechanisms by which inheritance can respond directly to environmental change, inviting a reanalysis of Kammerer's descriptions. Previous arguments for mere somatic plasticity have ignored the description of experiments showing heritable germ line modification. Alleged inadvertent selection associated with egg mortality can be discarded, since mortality decreased in a single generation, upon repeated exposures. The challenging implications did not escape the attention of Kammerer's noted contemporary, William Bateson, but he reacted with disbelief, thus encouraging fraud accusations. Nowadays, formerly puzzling phenomena can be explained by epigenetic mechanisms. Importantly, Kammerer described parent‐of‐origin effects, an effect of parental sex on dominance. Epigenetic mechanisms underlie these effects in genomic imprinting and experiments of transgenerational epigenetic inheritance. In the early 20th century, researchers had no reason to link them with the inheritance of acquired traits. Thus, the parent‐of‐origin effects in Kammerer's experiments specifically suggest authenticity. Ultimate proof should come from renewed experimentation. To encourage further research, we present a model of possible epigenetic mechanisms.